Effects of process-based versus outcome-based self-regulatory goals and self-monitoring on performance and self-efficacy. - Combatir, Cheryl C. (2001.)
This study was undertaken to determine the effects of self-regulatory and self-monitoring on performance and self-efficacy. It investigated whether there was a difference in the performance and self-efficacy of students who engaged in process-based and outcome-based self-regulatory goals and self-monitoring. It also intended to find out whether there was a significant interaction between types of self-regulatory goals and self-monitoring. Sixty (60) students, from a total of sixty-five (65) students, enrolled in two sections of Social Psychlogy under Dr. Cynthia J. Ticao, were randomly assigned to four (4) groups. A reading material was handed out to the participant. The topic was selected through a survey conducted to forty (40) undergraduate students who have taken up Social Psychology during the previous years. After studying the material the participants were given the test questionnaire and the Self-efficacy scale from which results were analyzed. The results were analyzed using a two-way Analysis of Variance (ANOVA). It showed that self-regulatory goals and self-monitoring as indicated by self-recording influenced performance but not self-efficacy. Results showed that there was no significant interaction effect between self-regulatory goals and self-monitoring on both performance and self-efficacy. The total mean score of process-based self-regulatory goals (X_1=20.10) is higher than the mean score of outcome-based self-regulatory goals (X_2=17.83) on performance. For self-monitoring as indicated by self-recording, the total mean score of the presence of self-monitoring (X_1=17.80) is lower than that of the absence of self-monitoring (X_=20.130 ) on performance. On self-efficacy, the total mean score of process-based self regulatory goals (X_=129.44) is higher than that of outcome based self-regulatory goals (X_2=127.60) and the total mean score of the presence of self-monitoring (X_1=128.37) is lower than that of the absence of self-monitoring (X_2=128.66). Therefore, there was a significant difference between the effects of process-based and outcome-based self-regulatory goals and self-monitoring on performance. There was no significant difference between the effects of self-regulatory goals and self-monitoring on self-efficacy.
Research Paper (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Peformances -- Processed based; Performances -- Outcome based